ANALISIS FAKTOR INTERNAL DAN EKSTERNAL KEPATUHAN MASYARAKAT MEMBAYAR PAJAK BUMI DAN BANGUNAN - Rahmawati Allyreza; Syahidah Mumtaz; Ipah Ema Jumiati (Epistemik Press, 2023)
Land and Building Tax is a type of tax where the value is relatively smaller than other types of taxes. PBB object is land and buildings. Even though the object is related to land and building ownership in the community, the community's compliance to pay for it is still low. This study aims to find out what causes low public compliance from internal and external faktors. Internal faktors are related to the condition and self of the community (WP) while external faktors are related to regulations, tax administration and sanctions. The method used in this study is descriptive qualitative, using in-depth interview data collection techniques. Analysis of the research data used the Triangulation method according to Miles and Huberman with research informants consisting of village officials in Padarincang District, the community as taxpayers, PBB P2 tax collectors and the head of the tax revenue section of the Serang District Regional Office of Revenue. The results of the study show that internal faktors have a dominant influence where the faktor is the lack of understanding of the public in paying taxes due to economic faktors, and external faktors come from weak administration of the tax system related to the uncertainty of the schedule and time for the distribution of SPPT PBB-P2 and the fines for PBB P2 taxes which are assessed low so as not to give a deterrent effect on society. Therefore, innovation is needed in the form of a socialization method that is more interactive and easily understood by the public so that there is an increased understanding of the obligation to pay land and building tax in rural and urban areas.